Kinerja Badan Narkotika Kabupaten terhadap Pencegahan dan Penanggulangan Penyalahgunaan Narkoba pada Masyarakat di Kecamatan Maritenggae Kabupaten Sidenreng Rappang - Mirnayani R; Lukman, Lukman; Kamaruddin Sellang (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this study was to determine how effective the performance of the District Narcotics Agency is and how many factors influence the performance of the District Narcotics Agency in preventing and overcoming drug abuse in the community in Maritenggae District, Sidenreng Rappang Regency. This study used a quantitative method with a population of the entire community of Maritenggae District (54,291 people). The sample consisted of 100 respondents, determined by the Slovin formula and random sampling. Data were collected through observation, questionnaires, and literature studies, then analyzed using the SPSS application. The results of the study showed that based on the recapitulation table of performance variables, it can be concluded that of the five performance indicators assessed, namely productivity, responsibility, service quality, responsiveness, responsibility and accountability, as many as 78.8 respondents assessed the effectiveness of the Performance of the District Narcotics Agency (BNK) in the